Antimicrobial Peptide Cec4 Eradicates the Bacteria of Clinical Carbapenem-Resistant Acinetobacter baumannii Biofilm - Liu, Weiwei; Wu, Zhaoying; Mao, Chengju; Guo, Guo; Zeng, Zhu; Fei, Ying; Wan, Shan; Peng, Jian; Wu, Jianwei (Frontiers in Microbiology, 2020)
The drug resistance rate of Acinetobacter baumannii increases year by year, and the drugs available for the treatment of carbapenem-resistant A. baumannii (CRAB) infection are extremely limited. A. baumannii, which forms biofilms, protects itself by secreting substrates such as exopolysaccharides, allowing it to survive under adverse conditions and increasing drug resistance. Antimicrobial peptides are small molecular peptides with broad-spectrum antibacterial activity and immunomodulatory function. Previous studies have shown that the antimicrobial peptide Cec4 has a strong effect on A. baumannii, but the antibacterial and biofilm inhibition of this antimicrobial peptide on A. baumannii carbapenem resistance is not thoroughly understood. In this study, 200 strains of CRAB were sensitive to Cec4 with an MIC of 4 μg/ml. Cec4 was strongly inhibitory and eradicated the biofilm formed by CRAB; the minimum biofilm inhibition concentration (MBIC) was 64-128 μg/ml, and the minimum biofilm eradication concentration (MBEC) was 256-512 μg/ml. It was observed that Cec4 disrupted the structure of the biofilm using scanning electron microscopy (SEM) and laser scanning confocal microscopy (CLSM). A comparative transcriptome analysis of the effects of the antimicrobial peptide Cec4 on CRAB biofilm clearance identified 185 differentially expressed genes, including membrane proteins, bacterial resistance genes and pilus-related genes. The results show that Cec4 regulates the CRAB biofilm through multiple targets. In conclusion, Cec4 may represent a new choice for the prevention and treatment of clinical infections, and also provide a theoretical basis for the development of antimicrobial peptide drugs.